Photoactuating artificial muscle from supramolecular assembly of an overcrowded alkene-derived molecular switch - Adrien Combe; Shaoyu Chen; Gianni Pacella; Marc C. A. Stuart; John Y. de Boer; Giuseppe Portale; Ben L. Feringa (Nature Communications)
Abstract The amplification of molecular motion along length scales for macroscopic muscle-like functions, based on supramolecular polymers, provides attractive opportunities ranging from soft actuators to responsive biomedical materials. Taking the challenge to reveal dynamic assembly parameters governing muscle functions, we present the design of a photoswitch amphiphile based on an overcrowded alkene-derived core, and developed supramolecular artificial muscles. Going from molecular motor amphiphile (MA) to switch amphiphile (SA), taking advantage of high thermal stability of the switch core, a self-recovering of bent SA artificial muscle is observed in post-photoactuation without external intervention. Eliminating molecular motions in SA artificial muscle during the post-photoactuation and aging process enables us to identify correlations between dynamic assembly transformations and macroscopic actuating functions. These findings provide insights into photoactuation and subsequent self-recovery mechanisms from the aspect of dynamic assembly process, which offers new opportunities for developing amphiphile-based supramolecular artificial muscles.